Fluorescent Organic Nanoparticles New Generation Materials with Diverse Analytical and Biomedical Applications - Wani, Waseem A. (SpringerBriefs in Materials,, 2018)
This book provides a critical review of recent advances in the development of fluorescent organic nanoparticles as materials of choice for the design and fabrication of sensors, bioimaging agents and drug delivery systems. The properties and functions of nanoparticles differ significantly from those of their parent entities or their bulk phases. Two of their most important features are their increased surface-to volume ratio, and the formation of surface structures differing from those in their bulk phases. In addition, the book discusses the synthesis of fluorescent conjugated polymers, self-assembled fluorescent nanoparticles, polydopamine nanoparticles, and aggregation-induced-emission or aggregation-induced-emission enhancement nanomaterials. In closing, the book provides an outlook on future research and development in fluorescent organic nanoparticles as smart materials with an impressive range of potential applications.